Determinants of dengue type 2 virus infection in the mosquito Aedes aegypti - Salazar Sánchez, Ma. Isabel, author; Beaty, Barry J., advisor; Olson, Kenneth E., advisor; Blair, Carol D., committee member; Black, William C., IV, committee member; Moore, Chester G., committee member (Colorado State University. Libraries, 2006)
Dengue represents a public health problem in 112 countries worldwide. The control of this mosquito-borne disease has been hindered by the fact that there are neither approved vaccines nor effective drugs available. Additionally, the mosquito eradication programs have failed and the vector has reemerged in areas where it had been previously eradicated. In this dissertation project, DENV determinants of infection in its primary vector, the mosquito Aedes aegypti, were investigated. Potential viral as well as vector determinants of infection were examined. The rationale for this research was that a better understanding of virus-vector interactions will enable us identification of new potential targets for virus transmission intervention. The kinetics of infection and dissemination in the mosquito revealed the nature of midgut infection by DENV-2 and the persistence of viral RNA in midgut epithelial cells. The analysis of virus dissemination exposed the tracheal system as a potential conduit. The infection of salivary glands occurred as early as 4 days after an infectious blood meal in a dose-dependent manner. Virus exhibited striking tropisms for salivary glands and mosquito head tissues. The correlation between DENV-2 clinical severity in humans and virogenesis in Aedes aegypti mosquitoes was investigated. Four viruses of the American/Asian genotype (Yucatan strains), which were isolated from cases of different clinical severity, were characterized in mosquitoes. The case severity caused by these viruses significantly correlated with the dissemination rates to head tissues and virus titers in Chetumal (coindigenous) mosquitoes. The phenotypic and genotypic analysis revealed surprising differences when the DENV-2 American/Asian genotypes were compared to a virus from the American genotype from the same geographic region, the Yucatan Peninsula. Dissemination rates by the DENV-2 American/Asian genotype greatly exceeded the ones caused by the member of the American genotype. Differences occurred in E protein and 3'UTR sequences. However, the 3'UTR exhibited the most significant changes, which included nucleotide substitutions in structurally crucial domains that participate in virus translation/replication. Finally, physiological and anatomical conditions could also be determinants of DENV-2 infection and dissemination in the mosquito vector. These include the pH in the mosquito midgut and the ingestion of cell-associated DENV-2.
Keywords: parasitology; entomology; microbiology; virology